Uncertainty of pipe flow friction factor equations. (September 2021) - Muzzo, Luiz Eduardo; Matoba, Gláucio Kenji; Frölén Ribeiro, Luís
Abstract: This paper presents the turbulent pipe flow analysis of the friction factor's uncertainty for two different experimental scenarios: high-precision and standard engineering instruments. One deduced the uncertainty function of the implicit Colebrook's correlation and five of the most accurate and fast explicit correlations. The joint propagation of uncertainties is evaluated, sorted and mapped for the probabilities of intersection of the Colebrook's uncertainties against the alternative correlations. The maps display the fastest to the slowest equation for standard engineering and high-precision instruments, respectively for 50% and 95% intersection. For the standard engineering instruments, the least accurate of the explicit correlations are applicable and within the Colebrook uncertainty bounds. The most accurate correlations are necessary for specific roughness and Reynolds'o domains cases and for high-precision research instruments. Results also show that, for high-precision scenarios with a 95% uncertainty fit, there is still room for improvement in the explicit correlations. Highlights: The friction factor's uncertainty analysis is performed for turbulent pipe flow. Two types of scenarios: high-precision and standard engineering instruments. Uncertainty function is deduced for Colebrook equation and five explicit correlations. The joint propagation of uncertainties is evaluated, sorted and mapped. Explicit correlation's equations for high-precision case can still be improved.